The Effect of Quranic and Hadith-Based Animated Video Media on the Understanding of Science Concepts in Fourth Grade Elementary School Students - Liza Septiani; Mega Adyna Movitaria; Wisda Rahmadinur; Zulkipli Lessy (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2026)
This research was motivated by students' low conceptual understanding of science subjects, which fell below the minimum grade point average (KKTP), namely 64 out of a standard of 70. The study aimed to determine the effect of using animated video media based on the Quran and Hadith on the conceptual understanding of science subjects in fourth-grade elementary school students. The method used was a quasi-experimental design with a one-group pre-test and post-test, with a sample of 29 students using saturated sampling. Data analysis included validity, reliability, normality, and homogeneity tests, as well as hypothesis testing using t-tests and simple linear regression. The results showed a t-test significance of 0.000 < 0.05 and a calculated t-value of 11.352 > t-table of 1.699, with a coefficient of determination (R²) of 0.632 (63.2%). The average student score increased from 64 to 82.4, with a learning completion rate of 89.7% (≥ 70). Thus, animated video media based on the Quran and Hadith has been proven effective in improving elementary school students' understanding of science concepts